Keep up with growing enrollment with automated processes. Issue 3 (May 2016) - Hope, Joan
Abstract : Student enrollment has grown quickly at Austin Peay State University without any increase in the size of the staff in the Registrar's Office. Telaina Wrigley has led the Registrar's Office to success in keeping up with the work by automating processes.